2013
DOI: 10.1186/1471-2164-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel comparative analysis of the contributions of genome reduction and heat shock to the Escherichia colitranscriptome

Abstract: BackgroundBoth large deletions in genome and heat shock stress would lead to alterations in the gene expression profile; however, whether there is any potential linkage between these disturbances to the transcriptome have not been discovered. Here, the relationship between the genomic and environmental contributions to the transcriptome was analyzed by comparing the transcriptomes of the bacterium Escherichia coli (strain MG1655 and its extensive genomic deletion derivative, MDS42) grown in regular and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 48 publications
(70 reference statements)
4
64
1
Order By: Relevance
“…Second, multiple deletions of the evolved genomic sequence in the laboratory clearly disturbed the cooperative accessory networks formed during evolution, thus leading to decreased fitness regardless of the remaining growing capacity. Additional steps for sequence optimization or complete systematic reduction of accessory networks was required to retain the growth fitness of the small genome, thus potentially explaining why the reduced genome MDS42 grew as fast as the wild type genome did in minimal medium 12 , 22 , 33 . Because MDS42 exhibited a fixed periodicity for efficient growth in the transcriptome 33 and the sequence differences from the MG1655 counterpart ranging from single nucleotide substitutions to complete deletions, 46 we assumed that either a successful systematic loss of accessory networks or the sequence optimization owing to the serial transfer was achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, multiple deletions of the evolved genomic sequence in the laboratory clearly disturbed the cooperative accessory networks formed during evolution, thus leading to decreased fitness regardless of the remaining growing capacity. Additional steps for sequence optimization or complete systematic reduction of accessory networks was required to retain the growth fitness of the small genome, thus potentially explaining why the reduced genome MDS42 grew as fast as the wild type genome did in minimal medium 12 , 22 , 33 . Because MDS42 exhibited a fixed periodicity for efficient growth in the transcriptome 33 and the sequence differences from the MG1655 counterpart ranging from single nucleotide substitutions to complete deletions, 46 we assumed that either a successful systematic loss of accessory networks or the sequence optimization owing to the serial transfer was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Rough measurements of a series of reduced genomes (constructed from W3110) have not indicated any significant differences in the growth rate on the basis of optical density (OD), 14 whereas a closely related study has reported increased cell division time in another reduced genome library (constructed from MG1655) 32 . In addition, the well-known “clean” genome (MDS42) 12 has a growth rate comparable to that of its parent wild type genome (MG1655) in minimal medium, 22 , 33 and no general trend has been observed between genome size and growth in rich medium 26 . Whether and how the genome reduction links to the bacterial growth is still in argument, due to the different thinking on growth cost and/or genome evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in bacterial evolution experiments, the results from different strains tended to follow the same proportionality law described by equation (2.5). It is interesting to note that such correlated changes in expression levels by genetic changes have also been suggested in several other studies [14][15][16]. Of course, it will be important to further confirm the relationship shown in equation (2.5) in more laboratory evolution experiments, and to also unveil the underlying genotype-phenotype map that achieves the common, restricted change in expression levels observed in the experimental data.…”
Section: A Variety Of Genetic Changes Could Lead To a Given Or Similamentioning
confidence: 92%
“…Owing to the high-dimensionality in phenotypic changes as well as the difference in timescales between adaptation and evolution, one might assume that it would be difficult to adequately address this question. However, our recently published theoretical study, as well as other recent studies, suggests the possible existence of such a relationship [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation